QuantumPath: A quantum software development platform. (23rd December 2021) - Hevia, Jose Luis; Peterssen, Guido; Piattini, Mario
Abstract: Quantum computing has experienced a breakthrough. Several companies are taking up the challenge of designing and manufacturing quantum computers, and the supply of tools for quantum software development is growing all the time. This article addresses quantum software development toolkits and introduces the 'QuantumPath' platform. In developing QuantumPath, our aim is to fulfil certain principles such as: agnosticism, extensibility, integration, independency, optimisation, scalability, security, usability and software engineering support. This article presents both the architecture itself as well as the main tools that compose QuantumPath, in order to illustrate the support which platform provides to the development and execution of quantum software.